Clinical audit of antenatal service provision in Nigeria (2011)
We audited records of 365 pregnant women whose mean age was 25.6 ± 5.6 years. Their mean gestational age at booking was 29.3 ± 2.7 weeks; their mean number of antenatal visits was 4.2 ± 2.3. Weight, blood pressure, and urine were checked on 97.3%, 95.1%, and 86.3% of the women respectively. Hemoglobin estimation was done on 19.2% of women; 34.8% received two doses of tetanus toxoid. Malaria prophylaxis and iron and folate supplements were provided to 263 (72.1%) and 293 (80.3%), respectively. Late booking was common, and antenatal service was inadequately equipped. Early booking and full implementation of preventive treatments are recommended. Support for detection of anaemia and immunization service is desirable.